2018
DOI: 10.1148/rg.2018180047
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Tissue Markers, Genomic Profiling, and Other Prognostic Factors: A Primer for Radiologists

Abstract: An understanding of prognostic factors in breast cancer is imperative for guiding patient care. Increased tumor size and more advanced nodal status are established independent prognostic factors of poor outcomes and are incorporated into the American Joint Committee on Cancer (AJCC) TNM (primary tumor, regional lymph node, distant metastasis) staging system. However, other factors including imaging findings, histologic evaluation results, and molecular findings can have a direct effect on a patient's prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 103 publications
1
28
0
Order By: Relevance
“…In addition, Huang et al (36) demonstrated that the risks of recurrence and death gradually increased when tumor size increased. By contrast, some studies suggested that smaller tumor size is associated with poor survival (37,38). Consistent with those, the results of this study showed that a larger tumor size was an independent prognostic factor of good outcomes (HR = 0.96, P < 0.01), which revealed that for every 1 mm increase in tumor size, the risk of death is reduced by 4%.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Huang et al (36) demonstrated that the risks of recurrence and death gradually increased when tumor size increased. By contrast, some studies suggested that smaller tumor size is associated with poor survival (37,38). Consistent with those, the results of this study showed that a larger tumor size was an independent prognostic factor of good outcomes (HR = 0.96, P < 0.01), which revealed that for every 1 mm increase in tumor size, the risk of death is reduced by 4%.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, not all cases of IBC show the typical US features indicated for certain biological characteristics, and variations may occur depending on the patient's individual characteristics. In the literature, it was reported that the tumor size, patient age, and nodal status were significantly associated with the biological characteristics of tumors . For instance, a tumor size larger than 2 cm was more common in human epidermal growth factor receptor 2 and triple‐negative subtypes of IBC; patients younger than 50 years showed more hormone receptor–negative cancers compared with older patients; and nodal metastases were more frequent in patients with the human epidermal growth factor receptor 2 subtype .…”
Section: Discussionmentioning
confidence: 99%
“…The status of a patient with respect to these prognostic markers is intended to guide clinical decision making about initiating adjuvant chemotherapy and/or endocrine therapy after initial treatment of the breast cancer, depending on the risk of distant recurrence of the cancer. 61 , 62 In the United States, Oncotype DX is the most widely used among these breast cancer assays, followed by MammaPrint. 63 Other prognostic markers discussed in the literature include MapQuant Dx, 64 the Theros breast cancer index, 65 the Rotterdam signature, 66 and the Invasiveness gene signature.…”
Section: Breast Cancer Overtreatment and Its Prevention: Role Of Progmentioning
confidence: 99%